2006
DOI: 10.1016/j.cmet.2006.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Adipose triglyceride lipase-mediated lipolysis of cellular fat stores is activated by CGI-58 and defective in Chanarin-Dorfman Syndrome

Abstract: Adipose triglyceride lipase (ATGL) was recently identified as an important triacylglycerol (TG) hydrolase promoting the catabolism of stored fat in adipose and nonadipose tissues. We now demonstrate that efficient ATGL enzyme activity requires activation by CGI-58. Mutations in the human CGI-58 gene are associated with Chanarin-Dorfman Syndrome (CDS), a rare genetic disease where TG accumulates excessively in multiple tissues. CGI-58 interacts with ATGL, stimulating its TG hydrolase activity up to 20-fold. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
861
2
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 791 publications
(891 citation statements)
references
References 36 publications
22
861
2
6
Order By: Relevance
“…Our data showed that the phosphorylation of HSL and expression of CGI-58 were increased in the tissue of the RRM rats. Phosphorylation of HSL is required for the activity of the enzyme and is mainly regulated by protein kinase A. CGI-58 is localized to lipid [24] . This information suggests that multiple pathways might be involved in the activation of HSL and ATGL under conditions of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed that the phosphorylation of HSL and expression of CGI-58 were increased in the tissue of the RRM rats. Phosphorylation of HSL is required for the activity of the enzyme and is mainly regulated by protein kinase A. CGI-58 is localized to lipid [24] . This information suggests that multiple pathways might be involved in the activation of HSL and ATGL under conditions of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…(CGI-58) [24] , a lipid droplet-associated protein that promotes the hydrolysis of triglycerides by activating ATGL. Therefore, we measured the abundance of ATGL and CGI-58.…”
Section: Enhanced Lipolysis In White Adipose Tissue In Rrm Ratsmentioning
confidence: 99%
“…In addition to perilipin, a number of PAT (perilipin/adipophilin/TIP47) family proteins have been identified on the lipid droplet and may contribute to the regulation of lipolysis [62]. Comparative gene identification (CGI)-58, another lipid droplet-associated protein, has been shown to colocalize with perilipin [63,64] and increase lipolysis by activating desnutrin/ATGL (discussed in the next section) [65].…”
Section: Hydrolysis Of Triacylglycerolmentioning
confidence: 99%
“…Also, ATGL and PNPLA3 share the highest homology of any patatin domain proteins. 2 Binding of ATGL to CGI-58 is well documented, 3 and PNPLA3 148M also colocalizes with CGI-58. 4 CGI-58 is felt to decrease liver fat content by binding to and activating ATGL and hence by increasing lipolysis.…”
Section: Potential Mechanism Underlying the Pnpla3 I148m -Hepatic Stementioning
confidence: 97%